Pengaruh Kelengkapan Diagnosis Tindakan Pada Kasus Persalinan Berdasarkan ICD-9CM Terhadap Tarif INA-CBGs Pada Pasien JKN - Husin Husin; Etrie Nilan Novia Sari (HB PRESS, 2019)
INA-CBG’s is an abbreviation for Indonesia Case-Base Group is an application that uses the hospital to make a claim to the government. Completeness of the contents of the patient file file is very important because in the medical record information contains certain diagnosis. Based on the results of a survey conducted by researchers obtained 70% incomplete primary action diagnostic file and 60% incomplete secondary action diagnostic file and no tariffs increase. This study aims to determine the Influence of diagnosis of actions in Childbirth Cases based on ICD-9CM against CBGs-INA rates on JKN Patients. This research uses analytical method with Chi-square test. The population in this study were all JKN patient files in childbirth cases at Ratu Zalecha Martapura Hospital in January-March 2018 of 186 patients., which uses a calculation Slovin, sample taken as many as 127 files using purposive sampling. Based on the results of bivariate analysis obtained there was an influence between the completeness file of the diagnosis of primary and secondary action against INA- CBGs rates on JKN patiens.